The efficacy of inhaled hypertonic saline in children with cystic fibrosis who receive daily DNase. - Gencoglu, M. Y.; Tugcu, G. D.; Soydas, S. S. Akyan; Cinel, G.; Emiralioglu, N.; Yalcin, E.; Dogru, D. (European Respiratory Soc Journals Ltd, 2022)
[Abstract Not Available]
International Congress of the European-Respiratory-Society (ERS) -- SEP 04-06, 2022 -- Barcelona, SPAIN